Executive control in spoken noun-phrase production: Contributions of updating, inhibiting, and shifting. Issue 9 (September 2016) - Sikora, Katarzyna; Roelofs, Ardi; Hermans, Daan; Knoors, Harry
The present study examined how the updating, inhibiting, and shifting abilities underlying executive control influence spoken noun-phrase production. Previous studies provided evidence that updating and inhibiting, but not shifting, influence picture-naming response time (RT). However, little is known about the role of executive control in more complex forms of language production like generating phrases. We assessed noun-phrase production using picture description and a picture–word interference procedure. We measured picture description RT to assess length, distractor, and switch effects, which were assumed to reflect, respectively, the updating, inhibiting, and shifting abilities of adult participants. Moreover, for each participant we obtained scores on executive control tasks that measured verbal and nonverbal updating, nonverbal inhibiting, and nonverbal shifting. We found that both verbal and nonverbal updating scores correlated with the overall mean picture description RTs. Furthermore, the length effect in the RTs correlated with verbal but not nonverbal updating scores, while the distractor effect correlated with inhibiting scores. We did not find a correlation between the switch effect in the mean RTs and the shifting scores. However, the shifting scores correlated with the switch effect in the normal part of the underlying RT distribution. These results suggest that updating, inhibiting, and shifting each influence the speed of phrase production, thereby demonstrating a contribution of all three executive control abilities to language production.